A comparative study of low multidirectional locked nailing and locking compression plating in management of distal tibia fractures - Pinnaka, Balakrishna; S., Shankarlinga; Kamath, K. Ramachandra; Danda, Rajashekar; Raju, M. Girish (International Journal of Research in Orthopaedics, 2018)
Background: Ideal management for distal tibial meta-diaphyseal fracture remains controversial, due to lack of adequate evidences about implants and multiple treatment modalities. Most commonly these fractures were dealt with either locking compression plate (LCP) or by multi directional intra-medullary nail (IMIL). Aim is to compare these two implants, to understand the mechanism and find out the ideal implant for the management of distal tibia fractures. Methods: This study is prospective and comparative done at the associated hospitals of KMC Mangalore, spanning a period of around 2 years (October 2014 to July 2016). All patients presented with distal tibial meta-diaphyseal fractures were included in the study. Patients were treated with either low multi directional IMIL nail or by LCP and followed up for a minimum period of 6 months. Outcome measures included Olerud Molander Ankle Score (OMAS), wound issues, union of the fracture and patient mobility. Results: 50 consecutive patients (mean age 40 years) were included in the study, divided equally into 2 groups. Group-A treated with multi directional IMIL nail and group-B with MIPPO plating. Mean functional OMAS score for nailing is 91 and for plating is 88. All fractures treated with nailing united within 6 months and 4% patient treated by plating goes mal union and 4% infected. Conclusions: For distal tibial fracture management, intra-medullary nailing proved reliable surgical option with regards to the OMAS score, fracture union and less infection rates.